Sanctuary city policies and Latinx immigrant mental health in California. (March 2023) - Nieri, Tanya; Ramachandran, Maithili; Bruckner, Tim; Link, Bruce; Ayón, Cecilia
Abstract: This quasi-experimental study examined whether "sanctuary city" policies are an effective mechanism for reducing mental health inequalities by immigrant origin status in Latinx populations in California. Ample evidence indicates that people experience mental health problems when restrictive immigration policies are imposed. It remains unclear whether sanctuary city policies can improve population mental health in the groups targeted by restrictive immigration policies: undocumented immigrant Latinxs, documented immigrant Latinxs, and native-born Latinxs. We combined data on California's 482 cities concerning whether and when they implemented a sanctuary policy with health data on approximately 142, 000 adults, 6400 adolescents and 13, 000 children from the multi-year California Health Interview Survey. After using propensity score matching to identify non-sanctuary cities comparable to sanctuary cities, we estimated respondent-level difference-in-differences models to determine whether sanctuary city policies had beneficial mental health effects on three age groups: adults, adolescents, and children during the period 2007–2018. There was a trend toward improved mental health in sanctuary cities after policy enactment, but the patterns of mental health in the three Latinx immigration sub-groups of each age group did not conform to our hypotheses. Buffering the adverse effects of harsh federal immigration policies may need to involve other approaches, such as expanded local mental health care access. We discuss these results in terms of alternative treatment interference, residents' policy awareness, the policy's capacity to address past health impacts, methodological issues, and potential policy momentum. Highlights: Sanctuary city policy did not reduce psychological distress, but it did not aggravate it either. The policy impact was not different for undocumented, documented, and native-born Latinxs. Buffering the effects of federal policies may require other approaches, such as expanded local mental health care access.